2016
DOI: 10.1002/adfm.201600613
|View full text |Cite
|
Sign up to set email alerts
|

Mussel‐Inspired Approach to Constructing Robust Multilayered Alginate Films for Antibacterial Applications

Abstract: The exceptional mechanical properties of the byssus—the fibrous holdfast of mussels that provides underwater adhesion—have potential applications in medicine and technology. The catechol–Fe3+–catechol interaction underlies the unique properties of mussel byssus and has emerged as a tool for developing functional hybrid materials such as pH‐responsive, self‐healing gels. Herein, the construction of functional alginate (Alg) film on a solid substrate inspired by mussel byssus is reported. The approach consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 36 publications
1
64
0
Order By: Relevance
“…The wide range of dopamine grafting is achieved by altering the molar ratios of alginate to dopamine. The UV–visible absorption spectroscopy at 280 nm of the alginate–dopamine polymer revealed a dopamine content of 26%, which is close to the dopamine content in Mfp‐3, and also is within the range of dopamine content reported in other dopamine conjugated alginate polymers …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The wide range of dopamine grafting is achieved by altering the molar ratios of alginate to dopamine. The UV–visible absorption spectroscopy at 280 nm of the alginate–dopamine polymer revealed a dopamine content of 26%, which is close to the dopamine content in Mfp‐3, and also is within the range of dopamine content reported in other dopamine conjugated alginate polymers …”
Section: Resultssupporting
confidence: 79%
“…The dopamine content in mussel foot proteins (Mfps) varies from 10% to 15% in Mfp‐1, 2% to 4% in Mfp‐2, 25% in Mfp‐3, 5% in Mfp‐4, and 30% in Mfp‐5, whereas Mfp‐3 and Mfp‐5 are the proteins that contact the surface and help mussels adhere to wet surfaces . Some research groups reported that the dopamine contents incorporated into alginate ranged from 10% to 42% . The wide range of dopamine grafting is achieved by altering the molar ratios of alginate to dopamine.…”
Section: Resultsmentioning
confidence: 99%
“…The UV–vis spectrum of FD‐C showed a characteristic peak at 280 nm, which was absent in the UV–vis spectrum of fucoidan ( Figure 2 ). The results indicate that fucoidan was successfully conjugated with the UV‐absorbing dopamine . The catechol content in FD‐C was quantified by comparing with a calibration curve, which was generated using dopamine solutions (Figure S1, Supporting Information), and it was found to be 12.4 wt%.…”
Section: Resultsmentioning
confidence: 96%
“…The former might have been caused by the symmetric and asymmetric stretching vibrations of methyl, methylene, and methine in the alkali lignin, and the latter likely consists of the C─O stretching vibration of alkali lignin. For PSF, a broad overlapped band around 3278 cm −1 can be attributed to catechol ─OH/N─H group stretching as the PSF became broader and blunter in comparison to SF, probably due to hydrogen bonding between the polydopamine and SF . A new peak at 1320 cm −1 appeared in the TSF spectra, which belongs to the C─O of aromatic nucleus stretching vibration in tannic acid …”
Section: Resultsmentioning
confidence: 97%